Survivability of Imaginal Forms of Deer Louse Flies (Diptera, Hippoboscidae) - A. I. Bakhtushkina (Российский паразитологический журнал, 2019)
The purpose of the research is to study the lifespan of Lipoptena cervi imaginal forms under exposure of different temperature conditions and humidity. Materials and methods. L. cervi caught in natural habitats and taken off from marals’ skin served as the material for the research. Overall, 38 samplings have been conducted, 18 thousand L. cervi have been sampled. Caught imagoes were put into mattresses after suffocation with ether-chloroform mixture; the most viable insects were used in experiments. Research for L. cervi lifespan except host of volatiles (not fed) and taken off from marals were conducted under exposure of different temperature conditions and humidity as well as in different types of cages, in wool on skins that were taken off. L. cervi were kept in small quantities in free cages made of capron mesh. Results and discussion. The winged forms under mid-mountain zone conditions of the Republic of Altai can be seen from June up to October; wingless forms (on the feeders’ body) can be seen from June of the current year up to June of the following year and including. Chrysalides are present in nature throughout the year, as L. cervi can’t hatch out from chrysalides of the previous year generation fast enough in June and July before the chrysalides of the new generation begin to appear. The weight of the hatched out L. cervi is 7.9-11.5 mg, they die if the weight is decreased up to 3.0-3.9 mg. It would appear that, the energy and water reserve is 4.9-7.6 mg per one insect. Young not fed L. cervi live rather longer than sexually mature insects. The L. cervi lifespan reliably increases without food as the humidity increases. The longest lifespan is when the humidity is about 60-80% and temperature is about 14-16°С. In laboratory conditions, at the air temperature of about 20-25°C, the humidity of about 60-80%, and moderate airing the chrysalis development lasts for 90 days on the average.